The price of power: a public choice approach to Hunter Biden’s art sales - Mixon, Franklin G. (Frontiers in Political Science, 2025)
This study examines the market for Hunter Biden’s art, with an eye toward the art’s value as a rent seeking device that benefitted Hunter and the wider Biden family. More specifically, this study asserts that the usefulness of Hunter Biden’s art sales as a rent- or transfer-seeking tool can be established in any one of three ways. First, Hunter Biden’s paintings have not generally been judged positively. In fact, the quality of his artwork has been widely panned by esteemed art critics from around the globe, particularly in relation to transaction prices. Second, although information on the buyers of Hunter Biden’s art has, by design, been hidden from the public, one of the two known buyers received a prestigious presidential appointment from then-U.S. President Joseph Biden shortly after making a purchase, clearly giving the sale a privilege seeking appearance. Third, although data on Hunter Biden’s art sales are relatively scant, some quantitative evidence is provided in this study indicating that sale prices of the art and U.S. President Joseph Biden’s monthly approval ratings are positively and significantly correlated, a result that is consistent with the public choice theory of rent seeking.